A proposed multiagent model for bus crew scheduling - Shibghatullah, Abdul Samad; Eldabi, Tillal; Kuljis, Jasna (2006)
Bus crew scheduling is a complex problem to solve because of the large number of resources that need to be managed, complexity of allocating crew shifts, rising cost of crew and unpredictability of trafﬁc and crew availability. This causes a difﬁculty to maintain an optimal schedule. Existing systems are excellent in producing optimal or near optimal schedules. However, to maintain such optimality for day-to-day operations, crew scheduling systems need to extend their capabilities by enabling crew reassignment, a feature that is not currently available in currently existing automated scheduling systems. The aim of this research is to model the crew reassignment process using agents and simulate agents’ behavior in order to establish ways of automating management of unpredictable events. The model should assist supervisor in managing everyday bus operations. The paper presents agents analysis and design using Gaia methodology.